METHODOLOGICAL FOUNDATIONS OF USING ARTIFICIAL INTELLIGENCE IN TEACHING ENGLISH AND ITS ROLE IN DEVELOPING COMMUNICATIVE COMPETENCE - Maftuna Shakhriyorova Shamsiddin qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This paper investigates the methodological foundations for using Artificial Intelligence (AI) in English Language Teaching (ELT) and examines how such pedagogical interventions contribute to the development of learners’ communicative competence. Drawing on empirical studies, systematic reviews, and teacher perspectives, the study identifies best practices, pedagogical affordances, and challenges, and reports on the effects of AI‐mediated learning on speaking ability, engagement, learner confidence, and methodological innovation. The implications suggest that appropriately designed AI tools, integrated with communicative methodology, can significantly enhance communicative competence, provided that teachers are supported, tasks are real‐world oriented, and assessment practices adapt.